RANCANG BANGUN MODEL WAHANA HOVERWING XHW-1 - Taufiq Mulyanto; Digit Mitra Baruna (National Institute of Aeronautics and Space - LAPAN, 2011)
Hoverwing craft is a combination of hovercraft and WiSE-craft. Hoverwing craft operation has transition phase from air cushion lift to aerodynammic lift, and vice versa. A Hovering model, named XHW-1, was designed and built to understand further the design problem related to this kind of vehicle and to observe the transition phase. To simplify construction, manufacture and testing, but without reducing the uniqueness of the vehicle, the model was designed to be operated on a flat surface. The design considered hovercraft related aspect and aircraft aspect as well. The configuration chosen was monohull. The model weight 755 gr, has 1.2 m wing span, and 20 x 30 cm air cushion. Preliminary test showed that air cushion could function properly and that model could reach 3 m/s forward speed. Keywords: Hoverwing, Hovercraft, WiSE-craft, Design, Model build